Two new species belong to genus Channa (Channidae, Perciformes) discovered in Ninh Binh province, Vietnam - Hao, Nguyen Van (Academia Journal of Biology, 2012)
Two news endemic locally species belong to genus Channa (Channidae, Perciformes) were discovered in Hoa Lu region, Ninh Binh province, including: 1. Channa hoaluensis Nguyen V. H. sp. nov. (figs. 1a, 1b) Holotype: NB.10.05.001(female); SL: 255 mm; collected in fish pond of the Research Institute for Aquaculture No.1 - Bac Ninh on 13th May 2010 (from fish collected in Truong An commune, Hoa Lu district, Ninh Binh province on 15th March 2008). Paratype: NB. 10.05.002 (female); SL = 223 mm; NB. 10.05.003 (male). Same data as holotype. Diagnosis: Mouth deep and narrow, arc length greater than width. 62-64 lateral line scales; 56-57 vertebrae. Gill rakers on first arc: 4-6. Tongue flad, sucking thin, slightly rounded shape provides of the mouth, body with 7-8 horizontal stripes. Discription: D = 48-49; A = 31-32; P = 14; V = 0; C = 13-14; L.l = 62. Scales surrounded caudal C = 22-24. Gill rakers 4 - 6. Vertebrae: 56 - 57. Lo = 6,14A = 3,63T. T = 4,79Ot = 6,91O = 3,44OO. OO = 2,00O. Body elongated, the front cylinder, the back side flat. Line of the back and abdomen slightly bent rim. Hilt of tail short and high. Head slightly longer and narrower. Deep and narrow mouth arc length greater than mouth dimensional rong. Tongue flat rim, thin tip slightly rounded, yet takes up the width of the mouth cavity (fig. 2: a, b, c). Dorsal fin long, starting at the beginning pectoral fins, to the snout tip with 1/3 to the caudal end. There are no ventral fins. Anal fin long, beginning with next snout to caudal fin base. Caudal fin rounded (table 1). Trunk and head with ctenoid scales. The scales on the chest and abdominal smaller than the trunk. Lateral line is not continuous, interrupted in the middle. Colour: dark gray back, pale gray belly. On the body are seven to eight horizontal stripes, the brackets (<). Remarks: This species is distinguished with other non pelvic fin species in genus Channa are: deep arch mouth, the length of the mouth is greater than the width. The gap before the dorsal fin is larger than the gap before the pelvic fin. There are more than 60 lateral line scales, 56 -57 vertebrae. Gill rakers on the fisrt arch: 4 - 6. Long tongue, flat, thick, suck is arc, close to lower jaw, the back shape is tapering, occupies the width of mouth cavity. There are 7 - 8 crossed bracket strips (<). There is a black spot after the gill cover and above the source of pectoral fin. Source of caudal fin has a black eyelike spot. Fish distributes in the water area of Hoa Lu district, Ninh Binh province. Distribution: C¸ sèng ë c¸c vïng ®Êt ngËp níc, ®Çm lÇy gi¸p víi c¸c nói ®¸ v«i vµ trong c¸c hang ®éng thuéc huyÖn Hoa L tØnh Ninh B×nh. Etymology: This species is named after the type locality. 2. Channa ninhbinhensis Nguyen V. H. sp. nov. (figs. 3 a, b) Holotype: NB.10.05.011 (female); SL = 275 mm; collected from fish pond of Research Institute for Aquaculture No1 - B¾c Ninh, on 7th May 2010 (from fish collected in Ninh Hai commune, Gia Vien district, Ninh Binh province on 20th April 2008). Paratype: NB 10.05.012 (male); SL = 267 mm & NB 10.5.013 (female); SL = 270 mm. Same data as holotype. Diagnosis: Arc of mouth wide, length less than width. The lateral line scales 58-59, vertebrae 51-52 units. Gill rakers on first arc: 8-12. Tongue flat, sucking thick circular arc, not accounting for all the mouth cavity width. Body dark gray, with no stripes. Description: D = 48 - 49; A = 28 - 32; P = 15 - 16; V = 0; C = 15 - 16. L.l = 58 - 59. 22 scales surrounded caudal peduncel. Gill rakers on I arch: 8 - 12. Vertabral bodies: 51 -52. Lo = 5,93H = 4,09T. T = 4,47O t = 7,10O = 3,22OO. OO = 2,22O. Body elongated, slightly rounded front, the back side flat. Slightly bent back rim. Abdomen with straight borders. Hilt of tail short and high. Top flat with, short of slightly wide ngang. Mouth large, shallow and wide arc length less than mouth width. Tongue flat, sucking thick circular arc, accounting width not over yet oral cavity (fig. 4: a, b, c). Dorsal fin long, starting at the beginning pectoral fins, the snout tip with 1 / 2 to caudal fin base. There are no ventral fins. Anal fin long, beginning near the snout tip than caudal fin base. Caudal fin rounded (table 2). Trunk and head with ctenoid scales. Lateral chest and abdomen smaller scales on the body. Lateral line is not continuous, interrupted in the middle. Colour: Body dark gray, gray belly body. No ribs on the body. Remarks: This species is similar to C. asiatica (Linnaeus,1758) due to non pelvic fin. Shallow arch mouth, the length is smaller than the width. Starting point of dorsal fin is after starting point of pectoral fin. There are less than 60 lateral line scales, 49 - 53 vertabrae. 8-12 gill rakers on the first gill arch. This new species differs from Channa hoaluensis .n.sp are: The gap from starting point of dorsal fin to tip of snout is larger than 1/2 to caudal fin. The starting point of anal fin is closer to snout tip than to caudal fin. Short head (Lo = 4.09T). The distance between two eyes is large. Eyes are larger (T = 7.1O), the tongue is flat, thick, tip of the tongue is arc and close to lower jaw, the back of tongue is gradually wide and occupies the width of oral cavity. Body is black grey without strip. Distribution: Fish distributes in water areas in three districts Hoa Lu, Gia Vien and Yen Mo in Ninh B×nh province. Etymology: This species is named after the name of the province local where type was collected.